The relationship between social aspects and the learning process at the Federal Institute of Mato Grosso - São Vicente Campus: Analysis of institutional contribution (Research, Society and Development, 2022)
In recent years, debates on school learning have expanded and started to be analyzed from the perspective of the contribution of the policy of permanence in Federal public education institutions. In this context, the Federal Institute of Mato Grosso - IFMT has a prominent role in promoting permanence actions in relation to the vacancies offered at the institution, identifying the relationship of student assistance with the institution's final objective. The descriptive qualitative research is committed to identifying the use of student assistance mechanisms within the IFMT from the perspective of full use for the successful result in the learning process of students of the technical course in agriculture integrated to the high school of IFMT Campus São Vicente. In this perspective, it was found that the IFMT Campus São Vicente is in a gradual process of improvement in relation to the use of student assistance linked to school performance. In addition to using student assistance from the perspective of social law, it has been presented as a tool for school retention.